Assessing a tertiary surgical units readiness to offer a fellowship in burn care in Africa - T. Netshiongolwe; S. Znamerovskyi; A. Muganza (Burns Open, 2024)
The number of patients presenting with burn injuries in Africa is increasing [1,2], and these injuries can have devastating outcomes [3,4]. One contributing factor to these outcomes is the lack of adequately trained staff in providing expert burn wound care. There is little emphasis on training staff in caring for burn patients in Africa. Our goal was to assess the services offered at a specialized burn unit in South Africa and compare them to the recommendations of the American Burn Association for providing fellowship training in burn care. Establishing such a fellowship program will help train experts who can improve burn care services across Africa.